Manajemen Pendidikan Teknologi Kejuruan dan Vokasi - Hadrian, Balqis; Siti, Yuni; Effendi, Muhammad; Amalia, Kaniati (TSAQOFAH, 2024)
Teaching and Vocational Technology Education Management" refers to the field of education management that is specifically concerned with the development, management, and improvement of vocational education systems. Background related to this topic may include some of the following aspects: Improving the Quality of Workforce: Vocational and vocational technology education is one of the main means of improving the quality of workforce. Improved quality of vocational education can help to produce workforce that is ready to work and has skills that fit the needs of industry and the labour market. Challenges in Curriculum Implementation, Vocational curriculum implementation requires good management. It covers planning, organization, guidance, and control of resources as well as vocational education processes, such as facilities, teachers, and teaching materials. Vocational management education often involves partnerships and close collaboration with industry. Effective management is needed in establishing relationships with companies and industrial organizations to ensure that vocation programs are tailored to the needs of the industry sector. The use of Technology in Learning, the use of technology in vocational education has become an important aspect. This includes technology infrastructure management, digital content development, as well as training and technology support for students and instructors.Certification and Accreditation, Vocational education management also involves certification and accreditation processes. This includes managing the process to ensure that vocational education institutions meet the standards set to provide quality education. Research and Innovation Vocational education management should also support research and innovation in learning methods, curricula, and meeting the needs of emerging industrial sectors. Financial Resource Management: Financial management in the context of vocational education is important, including the allocation of funds for equipment, facilities, and program development. Increased Participation: Vocational education management also includes efforts to increase student participation, including those from diverse social and economic backgrounds. Improving the image and sense of prestige of vocational education is an important aspect in vocational management. This can affect students' interest in enrolling and completing vocational programs. Professional and vocational technology education management plays a central role in addressing these issues and ensuring that vocational education contributes positively to the development of qualified labour force and economic growth. Teaching and Vocational Technology Education Management (TVET) is a discipline related to the management of educational and training programmes aimed at developing technical and practical skills required in various sectors of employment. It covers planning, organization, resource management, curriculum implementation, improvement of teaching quality, as well as evaluation and continuous development of vocational education programmes.